For a Ghoul Time, Call: Telephonic Terror at the Boundary of Narrative and Information in BBC Ghostwatch - Rose Rowson (ScholarWorks @ UMass Amherst, 2021)
This article revisits controversial BBC television film Ghostwatch (1992), a seasonal feature-length television special about a family plagued by a poltergeist and the television crew has entered their home hoping to capture ghostly phenomena on camera. Fictional, scripted, and filmed in its entirety prior to airing, Ghostwatch follows the formal conventions of live, factual television: well-known British media personalities host from the studio and on location, interviewing experts on the paranormal, and periodically inviting the watching public to call the show via the BBC phone-in number, 0818118181, which had both a diegetic and an actual function. The high volume of calls that the BBC received during the program caused the switchboard to jam, leaving reportedly tens of thousands of callers unable to speak to an operator.